New Report of Ascotis selenaria imparata Walk. (Lepidoptera: Geometridae) Infesting Pterocarpus marsupium Roxb. Plantation in Madhya Pradesh, India - Bhowate, Shalini; Meshram, P. B. (Indian Forester, 2019)
No Abstract.